2021
DOI: 10.1002/mma.7616
|View full text |Cite
|
Sign up to set email alerts
|

Optimal decay rates of a nonlinear suspension bridge with memories

Abstract: In this paper, we investigate the decay properties of suspension bridge with memories in one dimension. To prove our results, we use the energy method to build some very delicate Lyapunov functionals that give the desired results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…We can cite the works of [12] for the suspension bridge models with viscoelastic or memory, [23] for Kang's contribution on the global attractor to a thermoelastic suspension bridge equation with past history, and [29] for Mukiawa's contribution on the asymptotic behavior of the solutions of the suspension bridges with viscoelastic damping. Afilal et al [4] demonstrated the uniform decay of the thermoelastic suspension bridges model, and Afilal et al [2] demonstrated the general decay for the suspension bridge model with two memories.…”
mentioning
confidence: 99%
“…We can cite the works of [12] for the suspension bridge models with viscoelastic or memory, [23] for Kang's contribution on the global attractor to a thermoelastic suspension bridge equation with past history, and [29] for Mukiawa's contribution on the asymptotic behavior of the solutions of the suspension bridges with viscoelastic damping. Afilal et al [4] demonstrated the uniform decay of the thermoelastic suspension bridges model, and Afilal et al [2] demonstrated the general decay for the suspension bridge model with two memories.…”
mentioning
confidence: 99%